The Textual Linguistics Dictionaries In Arab culture -its models and forms of investment in discourse analysis– - hadjhenni, mohamed; Rougab, Jamila (El Omda in Linguistics and Discourse Analysis, 2025)
contributed to crystallizing the concepts of this linguistic field, controlling its terminology, and laying the parameters of its procedural approaches. This is on the one hand, and the identification of the cognitive, communicative and cultural objectives of these specialized dictionaries on the other hand.